2018
DOI: 10.1109/mits.2018.2806643
|View full text |Cite
|
Sign up to set email alerts
|

Smart Outdoor Light Desktop Central Management System

Abstract: Light pollution and nature preservation, are new trends in which the European cities are involved as they evolve into Smart Cities. Internet of Things are changing the way that sensors and management control systems are designed and implemented. In this article, our main objective is to present an Outdoor Light Desktop Central Management architecture using current IoT (Internet of Things) and GIS technologies to improve the energy efficiency, user experience and safety feeling at the same time we are going to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Kovács et al [107], developed a GUI that provides real-time status updates, customization of dimming levels, and system administration features, ensuring regulated access based on user roles. Dolores et al [123], proposed a smart central management system with a map-based GUI, allowing users to manage luminaires, configure light points, and access diagnostic tools for system failures. Abarro et al [124], offered a GUI that enables users to switch between various operational modes of the lighting system, ensuring customizable control based on specific needs.…”
Section: User-driven Controlmentioning
confidence: 99%
“…Kovács et al [107], developed a GUI that provides real-time status updates, customization of dimming levels, and system administration features, ensuring regulated access based on user roles. Dolores et al [123], proposed a smart central management system with a map-based GUI, allowing users to manage luminaires, configure light points, and access diagnostic tools for system failures. Abarro et al [124], offered a GUI that enables users to switch between various operational modes of the lighting system, ensuring customizable control based on specific needs.…”
Section: User-driven Controlmentioning
confidence: 99%
“…Its simulation results demonstrated that the average periodic maintenance time and the abnormal state of the server was approximately 20 minutes. Escrivá et al [20] put forward a prototype architecture based on IoT devices and cloud computing. The modules included: a dedicated wireless lighting controller, one IoT sensor gateway set installed on LED lights, a smart collector, and a central management system.…”
Section: Related Work a Smart Street Lightmentioning
confidence: 99%
“…In terms of the technologies used in GIS for smart street lighting, for example, the Outdoor light desktop central management architecture using Internet of Things (IoT) and GIS technologies is described in [8]. The remote controlled smart LED lighting system is proposed, for example, in [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LonMark (www.lonmark.org) presents a system architecture for dynamic street-light control, which relies on key components such as light point controllers, gateways (OLC), segment controllers, meters, sensors, digital and analogue inputs and other devices (www.lonmark.org). Although most of the above described solutions reduce the energy consumption, they are still too expensive [8] and thus difficult to apply to smaller towns lighting. That is why we propose the low-cost web-based GIS for smart lighting for smaller towns and villages.…”
Section: Introductionmentioning
confidence: 99%